Highly stable titanium–manganese single flow batteries for stationary energy storage. Issue 21 (26th March 2021) - Qiao, Lin; Xie, Congxin; Nan, Mingjun; Zhang, Huamin; Ma, Xiangkun; Li, Xianfeng
Abstract : A titanium–manganese single flow battery with low cost is designed for the first time and exhibits high efficiency and long life. Abstract : Manganese-based flow batteries have attracted increasing interest due to their advantages of low cost and high energy density. However, the sediment (MnO2 ) from Mn 3+ disproportionation reaction creates the risk of blocking pipelines, leading to poor stability. Herein, a titanium–manganese single flow battery (TMSFB) with high stability is designed and fabricated for the first time. In the design, a static cathode without the tank and pump is employed to avoid blockage of pipelines by MnO2 particles. Benefiting from the deceasing disproportionation reaction rate, MnO2 from the disproportionation reaction is fully utilized, realizing nearly two electron capacity. The novel TMSFB exhibits coulombic efficiency (CE) of over 99.0% at a current density of 40 mA cm −2 . Most importantly, the TMSFB can run stably over 1000 cycles without capacity decay, demonstrating very good stability. With low cost, high efficiency and long cycle life, TMSFBs exhibit remarkable potential for large scale energy storage.